DETERMINASI KEPUASAN MAHASISWA KELAS INTERNASIONAL IIB DARMAJAYA LAMPUNG - Betty Magdalena; Viola De Yusa (Jurnal Bisnis dan Manajemen (JBM), 2021)
In attracting international class students, IIB Darmajaya tries its best to give all the best to meet student satisfaction. English is an obligation for international class students in every given course, and they must graduate from that course. This study aims to determine the factors that determine the satisfaction of international class students of IIB Darmajaya and to determine what factors are the most dominant in the satisfaction of international class students. The population in this study were active students of IIB Darmajaya. The sampling method used in this study is non-probability sampling using a purposive sampling technique to obtain a sample of 100 respondents. The analytical tool used in this study is descriptive analysis. The results of the Importance Performance Analysis show the essential attributes, namely regarding students having problems, lecturers/employees can solve problems, the department always finds out what students need. Students feel safe with the final grades of lectures. In general, the student satisfaction index in the international class for the attributes tested is in the reasonably satisfying criteria.